Pengaruh Digital Literacy dan Locus of Control terhadap Minat Berwirausaha pada Mahasiswa Tingkat Akhir Fakultas Ekonomi dan Bisnis Universitas Telkom - Aulia Dwi Nanda; Kiki Sudiana (J-MAS (Jurnal Manajemen dan Sains), 2022)
The purpose of this research is to see how big the level of interest of entrepreneurship, digital literacy, and locus of control as well as interest of enterpreneurship partially and simultaneously in final year students of Faculty of Economics and Business Telkom UniversityThe research method used is quantitative method with data collection which gained by spreading questionnaire to 296 respondents. The respondents involved are final year students of the Faculty of Economics and Business. The questionnaire used in this research contain 37 statments with five points likert scale. Sampling methods used is nonprobability with purposive sampling technique. In explaining the result of the research, the data analysis technique used is descriptive analysis, multiple linear regression, hypothesis testing (T-Test and F-Test) and coefficient of determination. The results obtained in this study based on the results of the t test showed that digital literacy has a significant positive effect on interest of enterpreneurship and locus of control has a significant positive effect on interest of enterpreneurship. These results are proven by hypotheses that reject H0. Based on the f test obtained the results that there is a significant influence simultaneously between digital literacy and locus of control on interest of enterpreneurship. The coefficient of determination obtained with the value of R Squere of 44,9% means that digital literacy and locus of control have an influence on interest of enterpreneurship of 44,9%.